2002
DOI: 10.1192/apt.8.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Stigma

Abstract: ‘Medicine is a social science, and politics nothing but medicine on a grand scale.’ (Rudolph Virchov, 1848, quoted in Link & Phelan, 1996)Discrimination and prejudice against people with mental illnesses is ubiquitous, pernicious and wrong. The overwhelming case against such stigma has been recognised by initiatives from the UK government, the Royal College of Psychiatrists, the US Surgeon General, the World Psychiatric Association and many other organisations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…It is believed that an undesirable perception of difference can feed into the generation of stigma. 9 In this study a number of sources of stigma were identified which could have been reinforced by the students' negative perceptions of difference within the specialty. This is interesting in light of the finding that a powerful source of stigma was from other medical students who had already undertaken an attachment in psychiatry.…”
Section: Discussionmentioning
confidence: 96%
“…It is believed that an undesirable perception of difference can feed into the generation of stigma. 9 In this study a number of sources of stigma were identified which could have been reinforced by the students' negative perceptions of difference within the specialty. This is interesting in light of the finding that a powerful source of stigma was from other medical students who had already undertaken an attachment in psychiatry.…”
Section: Discussionmentioning
confidence: 96%
“…First, the lack of opportunity to ask personalized questions and engage in dialogue with the consumers potentially limited the ability to confront more complex stigmas such as controllability and blame. Such stigmas have been evidenced to be complicated by their relationship to limited and inconsistent education about etiology and treatment [63][64][65][66][67][68][69]. Another factor may be the fact that while the majority of MHCES were involved in both interventions the MHCEs in the direct contact workshops generally appeared to talk more substantially about their experiences with a variety of mental illnesses including psychotic, affective and anxiety disorders, than in the filmed interviews.…”
Section: Discussionmentioning
confidence: 99%
“…An illinformed positive opinion could ultimately lead to more discrimination. Smith (2002) referred to this as 'normalisation', emphasising that although differences cannot always be ignored, they can be accepted.…”
Section: Discussionmentioning
confidence: 99%